224k views
3 votes
Which expression is equivalent to (2^1/2 x 2^3/4)^2

2 Answers

6 votes
(2^1/2 x 2^3/4)^2
= (2^2/4 x 2^3/4)^2
= (2^5/4)^2
= 2^10/4
= 2^5/2
User ErocM
by
5.0k points
2 votes

Answer:

Given the expression:
(2^{(1)/(2)} * 2^{(3)/(4)})^2

Using:


  • a^n * a^m = a^(n+m)

  • (a^n)^m = a^(nm)

  • a^{(m)/(n)} = \sqrt[n]{a^m}


(2^{(1)/(2)+(3)/(4)} )^2

Simplify:


(2^{(5)/(4)})^2


2^{(5 * 2)/(4)} =2^{ (5)/(2)} =
\sqrt[2]{2^5} = \sqrt[2]{32} = 4√(2)

Therefore, the expression which is equivalent to
(2^{(1)/(2)} * 2^{(3)/(4)})^2 is:
4√(2) or
2^{(5)/(2) }



User Michael Baldry
by
5.7k points